The Bookkeeping System Policy and Literacy Movement in Indonesia - Putera, Prakoso Bhairawa; Ningrum, Sinta; Widianingsih, Ida; Rianto, Yan; Suryanto, Suryanto (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2022)
The paper aims to reveal the book system policy in Indonesia and the efforts made to increase interest in reading, including the movement undertaken to improve literacy in Indonesia. Identification and mapping have been executed through the regulatory survey method on the peraturan.go.id database, while slip and analysis have been exercised through content analysis. The paper provides empirical insights into the bookkeeping system and movement undertaken to improve literacy in Indonesia. National policies have supported the bookkeeping system in Indonesia. Meanwhile, to increase interest in reading, a literacy movement was initiated by President Susilo Bambang Yudhoyono on November 1, 2007, through the Law of the Republic of Indonesia Number 43 of 2007. Indonesia's literacy movement is